2017
DOI: 10.1111/myc.12718
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and oxidative stress in corneal tissue in experimental keratitis due to Fusarium solani: Amelioration following topical therapy with voriconazole and epigallocatechin gallate

Abstract: Combined antifungal and antioxidant therapy may help to reduce oxidative stress in fungal keratitis. Experimental Fusarium solani keratitis was induced by application of F. solani conidia to scarified cornea (right eye) of 16 rabbits (another four rabbits were negative controls [Group I]). Five days later, F. solani-infected animals began receiving hourly topical saline alone (Group II), voriconazole (10 mg/mL) alone (Group III), epigallocatechin gallate (EGCG, 10 mg/mL) alone (Group IV) or voriconazole and EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…Indeed, studies have shown that oxidative stress in the degenerating retinas is considerably higher than that of normal retinas. Apart from retinal degeneration, oxidative damage is also a key pathology of many other diseases, such as age-related macular degeneration, glaucoma, diabetic retinopathy (31), retinopathy of prematurity (30), dry eye syndrome (32), keratitis (33), and retinopathy after radiotherapy (34). Different antioxidants have been used in the clinic to treat patients with degenerative diseases (35).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that oxidative stress in the degenerating retinas is considerably higher than that of normal retinas. Apart from retinal degeneration, oxidative damage is also a key pathology of many other diseases, such as age-related macular degeneration, glaucoma, diabetic retinopathy (31), retinopathy of prematurity (30), dry eye syndrome (32), keratitis (33), and retinopathy after radiotherapy (34). Different antioxidants have been used in the clinic to treat patients with degenerative diseases (35).…”
Section: Discussionmentioning
confidence: 99%
“…The reports have been published in the literature showing the effectiveness of voriconazole in the animal model, 15 , 16 , 18 , 21 , 22 and most of the animal models used 3 days of a waiting period to initiate the treatment which is indicated for treating superficial infections. 15 , 16 , 21 A report suggested that filamentous fungi tended to grow toward the anterior chamber as the infection progresses.…”
Section: Discussionmentioning
confidence: 99%
“… 13 18 A few studies have used subconjunctival injection of steroids to suppress the local immunity before infection into the corneal stroma 19 21 while others used systemic immunosuppression of dexamethasone or cortisone to suppress the systemic immunity. 22 , 23 Hence, we have used an integrated approach to achieve a successful F. solani rabbit keratitis model and reported a useful, reproducible rabbit model of F. solani keratitis which we used to compare three commonly used commercially available antifungals.…”
mentioning
confidence: 99%
“…Treatment of infected mice cornea with baicalein significantly reduced fungal growth, biofilm formation, adhesion, and suppressing inflammatory responses via downregulating the thymic stromal lymphopoietin (TSLP)/TSLP receptor (TSLPR) pathway (Zhu et al, 2021). Epigallocatechin gallate (EGCG) is a polyphenol obtained from the green tea is known to have good antioxidant and anti-inflammatory activity (Ruban et al, 2018). Topical administration of voriconazole along with EGCG showed the inhibition of F. solani-induced keratitis by reducing the fungal growth and inflammatory responses.…”
Section: Antioxidantsmentioning
confidence: 99%